The punk singer: [videorecording (DVD)] : a film about Kathleen Hanna - Jett, Joan; Brownstein, Carrie, 1974-; Gordon, Kim, 1953-; Hanna, Kathleen, 1968-; Hanna, Kathleen, 1968- (IFC Films ; MPI Media Group, 2014)
A look at the life of activist, musician, and cultural icon Kathleen Hanna, who formed the punk band Bikini Kill and pioneered the "riot grrrl" movement of the 1990s.